HUBUNGAN LINGKAR PERUT, IMT DAN KONSUMSI MAKANAN MANIS DENGAN KEJADIAN DIABETES MELLITUS PADA ORANG DEWASA USIA 26-45 TAHUN DI DKI JAKARTA (ANALISIS RISKESDAS 2018) - Anisa Putri Etika Ramadena (2021)
Diabetes mellitus occurs, one of which is characterized by hyperglycemia that occurs due to insulin abnormalities or insulin action (Perkeni, 2015). The 2018 Riskesdas survey showed an increase in the prevalence of diabetes mellitus in people over 15 years of age. High carbohydrate intake can affect the incidence of diabetes mellitus. This is caused carbohydrates that have been broken down by the body into glucose will be circulated throughout the body and the glucose balance will be controlled by the pancreas by releasing the hormone insulin. If a insulin produced is few, the glucose level in the blood will be excess and increase the occurrence of hyperglycemia. This study aims to analyze the relationship between consumption of sweet foods, body mass index and abdominal circumference with the incidence of diabetes mellitus in adults aged 26-45 years in DKI Jakarta based on the Riskesdas 2018 analysis. The results of the bivariate test with chi square showed a relationship between consumption of sweet foods (p = 0,000), body mass index (p = 0,000) and abdominal circumference (p = 0,000) with the incidence of diabetes mellitus. It can be concluded that there is a relationship between consumption of sweet foods, body mass index and abdominal circumference with the incidence of diabetes mellitus in adults aged 26-45 years in DKI Jakarta.